Exploring the utilisation of drone technology in construction: insights and practices within the Sarawak Region / Ervina Donnis and Mohamad Nidzam Rahmat - Donnis, Ervina; Rahmat, Mohamad Nidzam (UiTM Press, 2025)
This study evaluates the application of drone technology in the construction industry, particularly in the Sarawak vicinity. Using a quantitative methodology, data were collected via a survey targeting construction professionals. The findings indicate that a majority of respondents are familiar with drone technology, with engineers being the primary users. Drones are utilised across various construction stages for tasks such as monitoring and inspection, preventing project delays, mapping, and compliance with safety regulations. The study also highlights several challenges, including weather limitations, battery life, security concerns, and operational complexity. Despite these challenges, drones offer significant advantages such as ease of control, immediate inspection capabilities, high-quality data collection, and enhanced worker safety. 74% of respondents acknowledged the ease of drone deployment, 80% noted their flexibility, 92% appreciated their ability to capture high-quality images, and 86% valued remote site access. The research concludes that while drone technology is recognised and utilised in the construction industry, further efforts are needed to promote its broader adoption through training and budget allocation for drone management.